Karakterisasi Performa Adsorben Cangkang Telur Pada Proses Penyerapan Logam Merkuri (Hg) - Miftahurrahmah, Miftahurrahmah; Ellysa, Ellysa; Suhendrayatna, Suhendrayatna (REACTOR: Journal of Research on Chemistry and Engineering, 2024)
Mercury (Hg) is a highly toxic heavy metal with no biological benefits, posing significant environmental and health risks upon exposure. This study investigates the adsorption characteristics of chicken eggshell-derived adsorbents for the removal of Hg from aqueous solutions. The adsorbent preparation involved washing, drying, calcination, and KOH activation. Results indicated that the 170-mesh size adsorbent exhibited the highest adsorption efficiency, achieving a 99.70% removal rate of Hg. adsorption capacity tests revealed values ranging from 79,90 to 88,90 mg/g, conforming to the Indonesian National Standard (SNI) for activated carbon. Functional group analysis using Fourier-Transform Infrared Spectroscopy (FT-IR) identified a significant increase in aldehyde and ketone groups post-activation. The adsorption process reached equilibrium within 90 minutes, with optimal removal efficiency observed at an initial Hg concentration of 3,0 mg/L. These findings suggest that chicken eggshell-based adsorbents are a cost-effective and efficient solution for mitigating Hg contamination in wastewater, offering a sustainable alternative to conventional methods.